MOTION GRAPHIC "AKHLAK" SEBAGAI MEDIA EDUKASI PENYIMPANGAN PERILAKU SOSIAL PADA REMAJA - Heki Aprianto (Jurnal Bahasa Rupa, 2019)
Adolescence is a transition from children to adulthood, usually this is a very vulnerable period for parents because at this age children begin to look for identity. Teenagers begin to want to have their own desires and no longer want to be regulated by parents because they already feel as adults. Environmental factors in the residence and school environment are very influential on the stability of development in adolescence. Teenagers who are out of control and unable to control themselves will very easily fall into social behavior deviations such as fighting with friends, brawl to drug abuse. To help the school and parents in overcoming this problem, media education needs to be deviated social behavior in adolescents based on visual multimedia. Visual multimedia technology was chosen because this media tendency is much easier to be accepted and understood by teenagers compared to just a lecture or seminar. The making of educational media for social behavior deviations in adolescents was built using motion graphic techniques. Then for the development method used is the Multimedia Development Life Cycle. The results obtained in this study in the form of motion graphics with the title of Morals with duration 00: 02:20.